Панченко П.П., Славов В.П., Шмарчук В.А. Аграрна історія України - Якименко, М.А. (Український історичний журнал, 2000)
Рецензія на книгу: Панченко П.П., Славов В.П., Шмарчук В.А. Аграрна історія України. Навч.посіб. - К., 1996. - 405 с.